Using a Prenatal Electronic Medical Record to Improve Documentation within an Inner-City Healthcare Network - Ghartey, Jeny; Lee, Colleen; Weinberger, Elisheva; Nathan, Lisa M.; Merkatz, Irwin R.; Bernstein, Peter S. (American Journal of Perinatology, 2014)
Objective To study the impact of a prenatal electronic medical record (EMR) on the adequacy of documentation.Study Design The authors reviewed paper prenatal records (historical control arm and contemporaneous control arm), and prenatal EMRs (study arm). A prenatal quality index (PQI) was developed to assess adequacy of documentation; the prenatal record was assigned a score (range, −1 to 2 for each element, maximum score = 30). A PQI raw score and PQI ratio—that controlled for which elements of care were indicated for a patient—were calculated and compared between the study arm versus historical control arm and then the study arm versus contemporaneous control arm.Results The median PQI raw score was significantly lower in the study arm compared with historical control arm; however, the PQI ratios were similar between these groups. The PQI raw score was similar in both the study arm and contemporaneous control arm; however the PQI ratio was significantly higher in the study arm when compared with the contemporaneous control arm.Conclusion Implementation of this prenatal EMR did not have a significant impact on completeness of documentation when compared with a standardized paper prenatal record. Adequacy of documentation seems to be related to the type of practice.
Keywords: electronic medical record; prenatal care; outpatient clinic